Beyond Strategy, Towards the Kingdom of God: The Post-Critical Reconstructionist Mission of the Emerging Church - Moritz, Joshua M. (Dialog, 2008)
The Emerging Church is a diverse global phenomenon which envisions a radical reforming of the theology and praxis of the broader Christian church in light of the philosophical and cultural shift from modernism to post-modernism. Differing from the evangelical New Paradigm seeker-sensitive Church's generational focus, and the organizational unity and routines of Mainline Protestant denominations the Emerging Church conversation endeavors to create committed, authentic, day-to-day communities that embrace ecumenical and ancient Christian theology and practices in order to live out the reality of the in-breaking kingdom of God. Though precise systemic theological unity within the Emerging movement is recognized as an elusive goal that is generally not even sought, the movement as a whole finds much in common with post-conservative and post-liberal theology, and shares a joint mission with those who have been called to the task of post-critical reconstruction.